CONCEPTUAL STUDY ON THE AYURVEDIC ASPECT OF ALLERGY - Sason, *Rajveer; Malviya, Anshu (AYUSHDHARA, 2016)
Term allergy is a hypersensitive immune response of body to some foreign proteins can be hereditary and can be develop without genetic involvement. Cause of allergy is the reaction of human beings to a number of allergens. Usually it is due to vitiated pita & blood. Low immunity is responsible for almost all types of allergies. In Ayurveda, allergy is correlated with various concepts especially Ama, Asatmya, Virudhahara. Various Acharyas has explained various causes and symptoms having similarity with allergy. The main cause of allergy is Ama or toxins produced by low digestive fire. Different symptoms are produced at different levels. Production of Ama can vitiate Rakta & Pitta or it can vitiate Kapha, producing different symptoms. Immunity also plays important role in the production of allergy. All types of proteins either in animals or food origins can cause allergy. It was with this idea that an ancient, Indian literature was reviewed to find out the role of the constitution of human body in relation to allergy. According to Ayurveda, if the body balance is maintained no allergic reactions are possible. According to Ayurveda the body balance is basically based on the balance of Tridoshas. This paper gives an idea about the concept of allergy in Ayurveda from the views of various Samhita and Acharyas.